Domestic Violence in the Criminology and Victimology Perspectives: Case Study in Kupang, East Nusa Tenggara - Siti Syahida Nurani; Dyah Adriantini Sintha Dewi; Joel Rey Acob Ugsang; Nurdin Nurdin; Heru Santoso Wahito Nugroho (Varia Justicia, 2022)
The state controls the interaction of family members within the scope of the household through Law Number 23 of 2004 on the Elimination of Domestic Violence. Domestic violence cases often happen in Kupang City, East Nusa Tenggara, Indonesia. This paper analyzes domestic violence in the criminology and victimology perspectives. This study uses the qualitative method with an empirical juridical approach. Based on the results of the discussion, in the criminological perspective, domestic violence is a crime in the form of an expression of physical or verbal strength that reflects aggressive actions and attacks one’s freedom or dignity. In the perspective of victimology, the role of the victim is the basis for the emergence of violence, which impacts the physical, psychological, and social aspects. In Kupang, domestic violence cases are usually triggered by victims, i.e. provocative victims. Thus, both victims and perpetrators are responsible. While in other cases, the position of the victim as the basis for the emergence of domestic violence does not exist at all.